The quality of school development - Abdul Kadir, Suhaida; Abdul Hamid, Jamaliah; Roslan, Samsilah (2004)
School development consists of planning, implementation and evaluation process in order to improve the students achievement. School development is crucial because it provides a framework for schools to improve the quality of their education. In this study, school development represents eight core areas: curriculum development, staff development, student development, physical resources, school image, school finance, school administration processes, and continuous improvement. This paper reports on administrators’ and teachers’ evaluation of the quality of their school development. The study was conducted in 40 schools involving 782 respondents. Findings from the study indicated that overall school development attained was high average and schools tend to concentrate on curriculum development, physical resources, administration processes and continuous improvement areas compared to staff development, student development, school image and school finance. Study results also suggested that there were differences perception between administrators and teachers towards the quality of school development in all areas.